Cervical Sagittal Alignment in Patients with Cervical Spondylotic Myelopathy: An Observational Study From the Canadian Spine Outcomes and Research Network. Issue 5 (1st March 2022) - Evaniew, Nathan; Charest-Morin, Raphaële; Jacobs, W. Bradley; Johnson, Michael; Bailey, Christopher S.; Christie, Sean; Paquet, Jérôme; Nataraj, Andrew; Cadotte, David W.; Wilson, Jefferson R.; Craig, Michael; Xu, Mark; et al.
Abstract : Supplemental Digital Content is available in the text Among 250 patients with cervical spondylotic myelopathy (CSM) from a prospective cohort study, there were no significant associations between cervical sagittal alignment parameters and any measure of health-related quality of life, function, or symptoms at 12-months after surgery. These finding suggest limited importance for cervical alignment in routine practice. Abstract : Study Design: Prospective cohort study. Objective: Among patients with CSM, we aimed to evaluate the extent to which: (1) Preoperative cervical sagittal alignment is associated with health-related quality of life, function, and symptoms; (2) Surgery leads to changes in cervical sagittal alignment; and (3) Postoperative cervical sagittal alignment is associated with health-related quality of life, function, and symptoms at 12 months of follow-up. Summary of Background Data: The importance of maintaining or improving cervical sagittal alignment in the surgical management of patients with CSM has not been established. Methods: We measured C2–C7 Cobb angle, T1 slope, and C2–C7 cervical sagittal vertical axis (cSVA). We tested for associations with Neck Disability Index, Pain Scales for neck and arm pain, EuroQol 5D, Short Form 12 Physical and Mental Component Summaries, and modified Japanese Orthopaedic Association scores. We adjusted for potential confounders using multiple linear regression, and we performed various prespecified subgroup (cSVA > 40 mm, surgical approach) and sensitivity analyses. Results: Among 250 patients, adjusted analyses yielded significant inverse associations prior to surgery between each of cSVA and T1 slope with SF12 Physical Component Summaries (T1 slope: −0.14, 95% CI −0.26 to −0.01, P = 0.03; C2–C7 cSVA: −0.13, 95% CI -−0.21 to −0.05 P < 0.01). Surgery was associated with a small but statistically significant increase in cSVA across the cohort (+5.8 mm [SD 11.7], P < 0.01) but no change in Cobb angle or T1 slope. At 12-months after surgery, there were no significant associations between alignment parameters or change in alignment and any measures of health-related quality of life, function, or symptoms. Results were consistent across subgroup and sensitivity analyses. Conclusion: Increased cSVA and T1 slope were associated with inferior health-related quality of life at presentation among patients with CSM, but no significant associations were observed following surgical treatment. Level of Evidence: 3